2014
DOI: 10.1111/1567-1364.12222
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and carbon assimilation bySaccharomyces cerevisiaeduring Sauvignon blanc juice fermentation

Abstract: To investigate the assimilation and production of juice metabolites by Saccharomyces cerevisiae during winemaking, we compared the metabolite profiles of 63 Sauvignon blanc (SB) grape juices collected over five harvesting seasons from different locations of New Zealand before and after fermentation by the commercial wine yeast strain EC1118 at 15 °C. Metabolite profiles were obtained using gas chromatography-mass spectrometry and nuclear magnetic resonance and the oenological parameters were determined by Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 73 publications
(108 reference statements)
5
20
0
Order By: Relevance
“…Gas Chromatography-Mass Spectrometry (GC-MS) was the first instrumentation used for metabolite profiling of human blood and urine by Horning in 1971 [8]. Since then, GC-MS has been applied to determine the metabolite profiles of many biological samples including plants, animals, and microorganisms [9,10,11,12,13,14]. As GC-MS has been used for metabolite profiling for over five decades, many protocols for machine set-up and maintenance are already available [9].…”
Section: Introductionmentioning
confidence: 99%
“…Gas Chromatography-Mass Spectrometry (GC-MS) was the first instrumentation used for metabolite profiling of human blood and urine by Horning in 1971 [8]. Since then, GC-MS has been applied to determine the metabolite profiles of many biological samples including plants, animals, and microorganisms [9,10,11,12,13,14]. As GC-MS has been used for metabolite profiling for over five decades, many protocols for machine set-up and maintenance are already available [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of sugars, together with other fundamental supplements, for example, amino acids and minerals, S. cerevisiae will conduct fermentative digestion to ethanol and carbon dioxide as the cells endeavor to make energy and recover the coenzyme NAD+ under anaerobic conditions . It is during this phase that the majority of the ethanol is excreted, and S. cerevisiae cells undergo even progressively distressing conditions and modulate their metabolic activities in order to adapt to these environmental changes . The yeast cells specially consume glucose when both glucose and ethanol were accessible, until the point that all the glucose was consumed totally .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, many metabolomics studies have been carried out to determine effect of juice or growth media composition on overall wine yeast metabolism, with particular attention on the developments of fermentation end products [107,108,141]. For instance, two publications from a research group of the University of Auckland reported changes before and after fermentation in Sauvignon blanc juices and how juice composition influences the major varietal aroma compound production by Saccharomyces cerevisiae EC1118 [34,107].…”
Section: Study Of Yeast Metabolism and Aroma Compound Development Durmentioning
confidence: 99%
“…Over the past decade, many metabolomics studies have been carried out to determine effect of juice or growth media composition on overall wine yeast metabolism, with particular attention on the developments of fermentation end products [107,108,141]. For instance, two publications from a research group of the University of Auckland reported changes before and after fermentation in Sauvignon blanc juices and how juice composition influences the major varietal aroma compound production by Saccharomyces cerevisiae EC1118 [34,107]. Based on a combination of comprehensive metabolite analysis by two different analytical platforms (GC-MS and NMR), they analyzed 63 grape juices and respective wines produced over six different seasons and showed that assimilation of different nitrogen and carbon sources by EC1118 depended on the overall grape juice composition [107].…”
Section: Study Of Yeast Metabolism and Aroma Compound Development Durmentioning
confidence: 99%